PENGEMBANGAN MEDIA PENDIDIKAN GIZI MELALUI KOMIK UNTUK REMAJA MENGENAI PENGETAHUAN GIZI TENTANG OBESITAS PADA SISWA SMPIT SAID NA'UM DI JAKARTA - Putriyus Adella Carolina Megasenja (2020)
Obesity in adolescents was high, it is crucial to provide a nutritional education to adolescents about obesity with a more interesting nutritional education media.This study was conducted to development of nutrition education media about obesity to teenagers with comics.This research uses the design of quasy experimental by providing pre-post treatment test. This study was conducted at SMPIT Said Na'um Central Jakarta, consisting of 40 respondents by means of simple random sampling. This study divided with 4 pashes, pre-test assesment, the assessment of the black and white comics, assessment the acceptability of color comics, and post-test. The result of nutrition education about obesity using a comic media was improved the nutritional knowledge about obesity with the results of good category knowledge increased 30%. The results of difference test showed that nutrition education about obesity using comic media has a significant difference on pre-test and post-test knowledge (P-0.000< 0,05). Nutritional education about obesity using comic media can improve nutritional knowledge about obesity. Keywords: Nutrition Education, Nutritional Knowledge, Comic, Obesity